Chapter 5 Treatment - Caws, Maxine (SpringerBriefs in Public Health, 2015)
This work contains updated and clinically relevant information about tuberculosis. It is aimed at providing a succinct overview of history and disease epidemiology, clinical presentation and the most recent scientific developments in the field of tuberculosis research, with an emphasis on diagnosis and treatment. It may serve as a practical resource for students, clinicians and researchers who work in the field of infectious diseases.